The joint effect of air pollution exposure and copy number variation on risk for autism. Issue 9 (27th April 2017) - Kim, Dokyoon; Volk, Heather; Girirajan, Santhosh; Pendergrass, Sarah; Hall, Molly A.; Verma, Shefali S.; Schmidt, Rebecca J.; Hansen, Robin L.; Ghosh, Debashis; Ludena‐Rodriguez, Yunin; Kim, Kyoungmi; Ritchie, Marylyn D.; et al.
Abstract : Autism spectrum disorder is a complex trait with a high degree of heritability as well as documented susceptibility from environmental factors. In this study the contributions of copy number variation, exposure to air pollutants, and the interaction between the two on autism risk, were evaluated in the population‐based case‐control Childhood Autism Risks from Genetics and Environment (CHARGE) Study. For the current investigation, we included only those CHARGE children (a) who met criteria for autism or typical development and (b) for whom our team had conducted both genetic evaluation of copy number burden and determination of environmental air pollution exposures based on mapping addresses from the pregnancy and early childhood. This sample consisted of 158 cases of children with autism and 147 controls with typical development. Multiple logistic regression models were fit with and without environmental variable‐copy number burden interactions. We found no correlation between average air pollution exposure from conception to age 2 years and the child's CNV burden. We found a significant interaction in which a 1SD increase in duplication burden combined with a 1SD increase in ozone exposure was associated with an elevated autism risk (OR 3.4, P  < 0.005) much greater than the increased risks associated with either genomic duplication (OR 1.85, 95% CI 1.25–2.73) or ozone (OR 1.20, 95% CI 0.93–1.54) alone. Similar results were obtained when CNV and ozone were dichotomized to compare those in the top quartile relative to those having a smaller CNV burden and lower exposure to ozone, and when exposures were assessed separately for pregnancy, the first year of life, and the second year of life. No interactions were observed for other air pollutants, even those that demonstrated main effects; ozone tends to be negatively correlated with the other pollutants examined. While earlier work has demonstrated interactions between the presence of a pathogenic CNV and an environmental exposure [Webb et al., 2016], these findings appear to be the first indication that global copy number variation may increase susceptibility to certain environmental factors, and underscore the need to consider both genomics and environmental exposures as well as the mechanisms by which each may amplify the risks for autism associated with the other. Autism Res 2017, 10: 1470–1480 . © 2017 International Society for Autism Research, Wiley Periodicals, Inc.